The Role of Teachers in Addressing the Bullying Phenomenon in the Digital Era for Generation Alpha in Elementary Schools - Suherman Suherman; Sri Handayani (MASI Mandiri Edukasi, 2026)
Bullying, including cyberbullying, has increasingly affected Generation Alpha students in elementary schools, creating challenges for teachers in maintaining a safe and child-friendly learning environment in the digital era. This study aims to analyse the roles of teachers and principals in preventing and addressing bullying through the implementation of G.R. Terry’s management functions: planning, organising, actuating, and controlling at SDN 1 and SDN 2 Pasirjaya. A qualitative approach with a descriptive case study design was employed. Data were collected through in-depth interviews, participatory observation, and documentation analysis involving principals, teachers, and students. The findings reveal that teachers and principals have implemented POAC-based management strategies by integrating bullying prevention into instructional planning, establishing collaborative anti-bullying teams, applying character education and digital literacy approaches in daily learning activities, and conducting continuous supervision through behavioural evaluations and digital reporting systems. These practices indicate that the systematic application of management functions enables educators not only to respond to bullying incidents but also to proactively foster a child-friendly school culture and strengthen students’ ethical behaviour in digital spaces.